Impacts of reward system towards job satisfaction and job retention among chefs in Kuala lumper - Syafiq Othman, Mohd.; Mohd. Sharil Nik Mohd. Nor, Nik; Fauzan Badiuzaman, Ahmad; Nizwan Abd. Majid, Hairul; Fata Talhah, Hasiful (International Journal of Engineering and Technology, 2018)
The purpose of the study is to investigate the impacts of reward system on job satisfaction and job retention amongst supervisor chefs working in four (4) and five (5) star hotel in Kuala Lumpur, Malaysia. Thirty eight (38) hotels in Kuala Lumpur were participated in this study. The samples collected represent supervisor chefs ranked demi chef de partie and above. Overall results found that chefs were really looking into and were satisfied with the reward system provided by the hotels. This study also suggests that hotels need to put more emphasize on reward system in retaining skillful employees. Since this study focused on supervisory level chefs, future study could expand to all levels of chefs working in hotel as well as other foodservice establishments.Â